2021
DOI: 10.3390/su13041741
|View full text |Cite
|
Sign up to set email alerts
|

Economic Sustainability and Multiple Risk Management Strategies: Examining Interlinked Decisions of Small American Farms

Abstract: Economic viability of small farms and farming businesses depends on multiple factors. These farms have limited production and financial resources to maintain their operation. Therefore, to sustain farming, adopting appropriate risk management strategies is a pivotal decision for small farmers. We surveyed Tennessee’s small farms and utilized multivariate probit models to study factors influencing the adoption of various risk management strategies. Our findings suggest that the decisions related to the adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In the face of digital agriculture and social media use for promotion, and to get and send information quickly, smartphones have been used in farm related businesses. Recent previous studies have included smartphone use in farm management and related decision models (Quandt et al 2020; Michels et al 2020; Adhikari and Khanal 2021). We found that a significantly higher number of diversified farms use smartphones in their farm-related activities and businesses as compared to specialized farms—around 85% of crop/livestock diversified farms and 89% of alternative on-farm enterprises adopter farms in our sample used smartphones in farm-related activities as compared to 62% specialized farms.…”
Section: Resultsmentioning
confidence: 99%
“…In the face of digital agriculture and social media use for promotion, and to get and send information quickly, smartphones have been used in farm related businesses. Recent previous studies have included smartphone use in farm management and related decision models (Quandt et al 2020; Michels et al 2020; Adhikari and Khanal 2021). We found that a significantly higher number of diversified farms use smartphones in their farm-related activities and businesses as compared to specialized farms—around 85% of crop/livestock diversified farms and 89% of alternative on-farm enterprises adopter farms in our sample used smartphones in farm-related activities as compared to 62% specialized farms.…”
Section: Resultsmentioning
confidence: 99%
“…As diversifying the income of a farm can provide financial stability to the small farm operation [17], farm operators are interested in income diversification tools for risk management. Farm operators have an interest in multiple risk management strategies [44], and perhaps they choose strategies such as agritourism to provide sustainability to the performance of their farms.…”
Section: Model Estimation Results For Factors Influencing Agritourism...mentioning
confidence: 99%
“…Smaller farms tend to rely more on off-farm income than larger farms and derive more than half of their total household income from off-farm revenue [25]. Further, their farms' operating profit margins are less than 10%, posing high financial risks [26]. They are expected to compete with the industrialized agri-food systems and comply with the norms of the capitalistic systems for accessing resources, markets, and rewards [27,28].…”
Section: Small-scale and Beginning Farmers In The United Statesmentioning
confidence: 99%